Breaking the myth: the association between the increasing incidence of labour induction and the rate of caesarean delivery in Finland - a nationwide Medical Birth Register study - Mika Gissler; Seppo Heinonen; Heidi Kruit; Leena Rahkonen (BMJ Open)
Objectives To determine the association between the rate of labour induction and caesarean delivery.Design Medical Birth Register-based study. We used data from the nationwide Medical Birth Register collecting data on delivery outcomes on all births from 22+0 weeks and/or birth weight of at least 500 g.Setting Finland.Participants 663 024 live births in Finland from 2008 to 2019.Main outcome measures The rates of labour induction and caesarean delivery.Results The rate of labour induction increased from 17.8% to 30.3%; p<0.001, during the study. The total caesarean delivery rate was 16.5% (n=109 178). An increase of approximately 0.5% in the caesarean delivery rate occurred during the study period. The rate of caesarean delivery following labour induction slightly decreased (15.41% vs 15.35%; p<0.001). In multivariate logistic regression analysis, induction of labour was associated with a reduced risk for caesarean delivery (OR 0.72, 95% CI 0.71 to 0.74). The frequency of advanced maternal age (18.0% vs 23.5%; p<0.001), obesity (11.4% vs 15.1%; p<0.001) and gestational diabetes (9.8% vs 23.3%; p<0.001) increased during the study.Conclusions The 70% increase in the rate of labour induction in Finland has not led to a significant increase in the rate of caesarean delivery, which has remained one of the lowest in the world. Pregnant women in Finland are more frequently obese, older and diagnosed with gestational diabetes, which may partly explain the increase in the rate of labour induction.